Leadership in context: Insights from a study of nursing in Western Australia. (May 2013) - Lord, Linley; Jefferson, Therese; Klass, Des; Nowak, Margaret; Thomas, Gail
This paper investigates the importance of integrating context when analysing the role and practice of leadership within a specific organization or profession. It does this with reference to a study of nursing in Western Australia. Using theoretical sampling, qualitative data were collected through interviews and focus groups with targeted stakeholders in Western Australia's public health system. The main purpose of the data collection and analysis was to identify perceptions and understandings of leadership among key stakeholders. Findings emerged which identified the importance of considering specific dimensions of the cultural, social and institutional context in order to understand the practice and experience of leadership among nurses in the Western Australian public health sector.